Self-Disclosure on Personal Information in Virtual Rental Relationships on Telegram - Reggina Putro; Lady Joanne Tjahyana; Felicia Goenawan (School of Communication Science and Media Business, 2025)
The phenomenon of boyfriend or girlfriend rental services, which initially emerged in Japan, has now expanded to Indonesia, driven by globalization and advances in technology. However, this rental concept has evolved beyond just hiring a boyfriend or girlfriend–it now includes the option to rent family members, friends, siblings, cosplay partners, and even types of relationships previously unimaginable. Within these virtual rental relationships, interactions can develop into emotionally intimate and meaningful connections, despite their transactional nature. Telegram, as a platform, offers advantages such as large-scale community features, bots, customizable forms, and group chats, which support the growth of this practice. This study identifies specific rental communities on Telegram that cater to users seeking rental services across Indonesia. The research focuses on the process of self disclosure, particularly how individuals share personal information within the context of virtual rental relationships on Telegram. Using a qualitative case study approach, this study involved two informants who are active members of rental communities and are currently occupied in rental sessions with partner(s). The findings reveal that motivation, gradual strategy, topic variation, emotional impact and risks all significantly influence how self disclosure is carried out, as well as how much and how deep personal information is shared.